The implementation of RBL-STEAM with pictorial riddle and augmented reality in improving students' historical thinking skill - Sumardi; Dafik; Mursyidah, Indah Lutfiyatul; Jannah, Excelsa Suli Wildhatul; Ridlo, Zainur Rasyid (Edelweiss Applied Science and Technology, 2024)
The purpose of this study is to analyze how the integration of the RBL-STEAM learning model with the Pictorial Riddle method, supported by Assemblr-Edu media, can enhance students’ historical thinking skills in world history courses. This research employs a hybrid methodology, combining qualitative and quantitative approaches. A pretest-posttest nonequivalent group design was utilized, where two groups received different educational interventions. The experimental group was exposed to the RBL- STEAM model integrated with the Pictorial Riddle technique and Assemblr-Edu media, while the control group received only the standard RBL-STEAM instruction. The integration of RBL-STEAM with the Pictorial Riddle technique and Assemblr-Edu media significantly enhances students' abilities to critically analyze, contextualize, and interpret historical events and sources. This approach not only fosters deeper engagement and understanding but also demonstrates a marked improvement in historical thinking skills compared to traditional RBL-STEAM methods. Additionally, student experiences were further analyzed using NVivo software, and Smart-PLS was employed to explore the relationships between RBL-STEAM variables and historical thinking skills. The analysis of the post-test data using SPSS and the independent samples t-test revealed a significant Sig value of 0.015 (<0.05). This indicates a statistically significant difference in the historical thinking skills scores between the experimental and control groups, with the experimental group showing superior outcomes. The results of the study indicate that implementing the RBL-STEAM model of teaching through the use of pictorial riddle and its integration with the Assemblr-Edu augmented reality learning media may enhance students' historical thinking abilities.